SELF-EVALUATION OF ADMINISTRATIVE WORK AND ITS RELATIONSHIP WITH ACCUMULATED PROFESSIONAL EXPERIENCES AMONG MEMBERS OF SPORTS CLUBS’ ADMINISTRATIVE BODIES IN THI QAR GOVERNORATE - Dr. Ali Hussein Halul (Galaxy International Interdisciplinary Research Journal, 2024)
The present research aims to analyze the intricate relationship between self-evaluation in administrative work and the accumulation of professional experiences. The researcher employed descriptive and survey methods to gather the necessary data. It is noteworthy that individuals who constitute part of administrative bodies were the subjects of this study. When evaluating themselves, these individuals generally exhibit an average level of self-assessment. Furthermore, it is important to mention that a positive correlation emerges when considering self-evaluation in administrative work and the accumulation of professional experiences. Essentially, this paper aims to delve into the relationship between self-evaluation in administrative work and accumulated professional experiences. The researcher used both descriptive and survey methods for data collection. Interestingly, members of administrative bodies, when assessing their work, typically display an average level of self-evaluation. Additionally, the results of this study reveal a positive correlation between self-evaluation in administrative work and the accumulation of professional experiences .